Kate Burkholder : After the Storm - Book 7 - Castillo, Linda (Thorndike, Maine : Center Point Large Print, 2015)
"When a tornado tears through Painters Mill and unearths human remains, Chief of Police Kate Burkholder is tasked with the responsibility of identifying the bones and finds herself plunged into a thirty year old murder case that takes her deep into the Amish community to which she once belonged"--
Keywords: Burkholder, Kate (Fictitious character) -- Fiction; Women police chiefs -- Fiction -- Ohio; Cold cases (Criminal investigation) -- Fiction; Amish -- Fiction -- Ohio; Large type books; Mystery fiction; Suspense fiction